Pengaruh Adopsi Marketplace dan Digital Payment terhadap Pendapatan Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Bandar Lampung - Mutia Ramadhani; Ade Widiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of marketplace and digital payment adoption on the income growth of MSMEs in Bandar Lampung City. The research employed a quantitative approach using primary data collected through questionnaires and interviews with 201 culinary MSME actors determined using the Slovin formula, which were then analyzed using multiple linear regression. The results show that marketplace adoption has a positive and significant effect on MSME income (t = 10.447; sig. 0.000), as does digital payment (t = 11.544; sig. 0.000), with digital payment being the most dominant variable (β = 0.511) compared to marketplace (β = 0.462). Simultaneously, both variables have a significant effect, with an F value of 232.111 and an R² of 0.701, meaning 70.1% of the variation in MSME income is explained by these two variables. These findings imply that the integrated optimization of marketplace and digital payment can serve as an effective strategy for MSME actors to expand market access and increase income, while also providing a basis for the government and digital service providers to design more targeted MSME digitalization literacy programs.